Embedding Safe System in Victoria: Blockers, Enablers and Improvement Roadmap - Hafez Alavi; Chris Jones; Carly Hunter (Journal of Road Safety)
The Safe System approach was adopted in Victoria in 2004. It has since been the cornerstone of every road safety strategy and action plan, most recently the Victoria Road Safety Strategy 2021-2030. Despite the absence of extensive and conclusive evidence, it is apparent that the limited integration of the Safe System approach into our road and transport management system has hindered its capacity to significantly reduce serious road trauma. In this project, five workshops were delivered by HA Consulting and Road Safety Victoria (RSV) to diagnose what implementation blockers exist and how road safety management systems and stakeholders could be enabled to implement the Safe System approach. Over 60 representatives attended the workshops from key road safety stakeholders and players. The anonymous workshop exercises identified a high personal alignment to the Safe System principles, a range of systemic practical day-to-day blockers, and suggestions for what could enable better Safe System aligned decision making. An improvement roadmap of concept-level projects was developed to address Safe System implementation blockers and implement the identified enabling measures.